2012
DOI: 10.1002/jcb.24069
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonate 5 lipoxygenase expression in papillary thyroid carcinoma promotes invasion via MMP‐9 induction

Abstract: Arachidonate 5-lipoxygenase (ALOX5) expression and activity has been implicated in tumor pathogenesis, yet its role in papillary thyroid carcinoma (PTC) has not been characterized. ALOX5 protein and mRNA were upregulated in PTC compared to matched, normal thyroid tissue, and ALOX5 expression correlated with invasive tumor histopathology. Evidence suggests that PTC invasion is mediated through the induction of matrix metalloproteinases (MMPs) that can degrade and remodel the extracellular matrix (ECM). A correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 38 publications
(91 reference statements)
1
44
0
Order By: Relevance
“…Increased expression levels of MMPs are associated with a number of cancers. Recent study demonstrates that arachidonate 5 lipoxygenase expression in papillary thyroid carcinoma promotes invasion via MMP‐9 induction . There is compelling evidence to suggest that MMP9 plays important roles in tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased expression levels of MMPs are associated with a number of cancers. Recent study demonstrates that arachidonate 5 lipoxygenase expression in papillary thyroid carcinoma promotes invasion via MMP‐9 induction . There is compelling evidence to suggest that MMP9 plays important roles in tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study demonstrates that arachidonate 5 lipoxygenase expression in papillary thyroid carcinoma promotes invasion via MMP-9 induction. 27 There is compelling evidence to suggest that MMP9 plays important roles in tumor invasion and metastasis. The design of new drugs to inhibit MMP expression levels is, therefore, a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies showed that 5-HETE promoted cancer cell migration by increasing the expression of MMP-9. 41 However, we found that 5-LOX metabolites from hypoxic ovarian cancer cells enhanced the expression of MMP-7 to promote the invasion of macrophages. Besides, MMP-7 was also highly expressed in macrophages close to the hypoxic area in the human ovarian tumor.…”
Section: Discussionmentioning
confidence: 97%
“…1 A small number of studies have recently suggested that 5-LO pathway metabolites are involved in the progression of various types of cancer, including prostate cancer, 2,3 pancreatic cancer, 4 esophageal cancer, 5 hepatocellular carcinoma, 6 and papillary thyroid carcinoma. 7 Recent studies have reported the strong immunoreactivity of 5-LO in Purkinje neurons, certain glial cells in the cerebellum, and parts of brain tumors. 8,9 Currently, no reports have been made on the immunoreactivity status of 5-LO in normal and neoplastic tissues of the human choroid plexus.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have used immunohistochemistry to show cytoplasmic staining for 5-LO in a subset of cells in CNS tumors. 7,9 Researchers have suggested that a decrease in LT C4 synthesis or increase in interleukin 5 could trigger the translocation of 5-LO to the nucleus in human blood eosinophils, 21,22 but the mechanism of this translocation between nucleus and cytoplasm in tumor cells remains unclear. In this study, we found that most types of brain tumors, including astrocytic, oligodendrogliomatous, ependymal, embryonal, and meningeal tumors, exhibited predominantly nuclear 5-LO staining, with weakly positive cytoplasmic staining in a small number of cases.…”
Section: Discussionmentioning
confidence: 99%